Cognitive dissonance as factor of influence in American courtroom discourse - Pelepeychenko, Lyudmyla; Zatsnyi, Yurii; Zaitseva, Margaryta (Linguistics and Culture Review, 2021)
The article reveals the specificity of cognitive dissonance in courtroom discourse as one of the mechanisms of communicative influence on the recipients. Two types of the phenomenon in question are grounded: dissonance caused by real-life facts, which include the nature of the crime itself, and dissonance artificially created by the prosecutor and the defense lawyer to persuasively influence the jury and the judge. Common is the use of a narrative as a persuasive, arousing the associative activity of the recipients by contrasting the axiological features of the concepts; combining elements of rational and emotional communicative influence. Distinctive features include the communicative strategies and tactics used by speakers and the choice of concepts around which communicative influence is modeled. The speeches of the prosecutor and the defense lawyer represent a kind of battle of narratives and a contest of cognitive dissonance. The research results in the following findings: the narrative that not only causes cognitive dissonance but also implicitly presents a way to overcome psychological discomfort and harmonize elements of the cognitive structure in the minds of the recipients wins.